Hubungan Pola Asuh Orang Tua dengan Kemandirian Personal Hygiene pada Anak Retardasi Mental Di SLBN Bangkinang Kota - Safitri , Rindiani; Syahda , Syukrianti; Lestari , Rahmawati (Evidence Midwifery Journal, 2023)
Prevalence data for persons with disabilities in Indonesia in 2019, namely mental retardation or mental retardation is in second place with blind people at 0.17%, mentally retarded at 0.14%, speech impaired at 0.14%, down syndrome at 0.13%, physically disabled at 0.08 %, and deaf 0.07%. The aim of this study was to determine the relationship between parenting parents and the independence of personal hygiene of mentally retarded children at SLBN Bangkinang Kota in 2022. Research time 31 August-06 September 2022. The population of this study is all parents who have children with mental retardation class I-VI in SLBN Bangkinang City with a total of 45 people. While the sample in this study is part or representative of the population to be studied. The sampling technique uses total sampling. Measuring tool used is a questionnaire. The analysis used is univariate and bivariate, processed using a computerized system. Based on the results of the study, it was shown that, out of 45 mothers who had mentally retarded children, most of the parenting styles were lacking, 25 people (55.6%) and independent personal hygiene for mentally retarded children, 27 people (60%). Based on statistical tests with the chi-square test, it was obtained that p value = 0.002 ? (0.05) meaning that there is a significant relationship between parenting styles and personal hygiene independence in mentally retarded children at SLBN Bangkinang Kota in 2022. It is hoped that parents will can apply independent personal hygiene to children, and take the time to provide support, enthusiasm and participate in teaching their children to have independent habits